Assessing Interventions for Declining Childhood Immunization Dropout - A Systematic Review - Jaleha, Jaleha; Widjarnarko, Bagoes; Susanto, Henry Setyawan; Margawati, Ani; Hadisaputro, Suharyo; Hikmah, Kholisotul (JURNAL INFO KESEHATAN, 2023)
Childhood routine immunization is a critical stage to ensure the health of infants and protect against serious diseases. Therefore, adequate strategies are urgently needed to increase childhood immunization coverage to prevent global disease and death. This review has identified the effect of interventions to increase immunization coverage among children in developing countries. A review included published studies from 2013 to 2023 on randomized controlled trials (RCT) and pre-post intervention that met eligible criteria. All included studies had been conducted in English-published articles on Pub Med and Google Scholar, without being limited to geographical sites. A total of 1107 published articles were accessed and 12 final eligible articles were reviewed. 66.67% of the included studies were conducted in Africa, 16.67% in South East Asia countries, and others were conducted in East Asia and America. These studies demonstrated that different interventions (SMS and call reminders, sticker reminders, immunization education, home-based records, and community-centered) had significant increases in immunization coverage for childhood compared to the control group with standard care or without any interventions. The present findings suggest that interventions including implementing SMS and call reminders, sticker reminders, education both from health workers and local leaders, and home-based records can potentially reduce immunization dropout. However, strategies to improve coverage for immunization uptake should also be considered preferred community-based to extend the marginal groups.